2014
DOI: 10.5301/ejo.5000527
|View full text |Cite
|
Sign up to set email alerts
|

Posteriorly Enclavated Iris Claw Intraocular Lens for Aphakia: Long-Term Corneal Endothelial Safety Study

Abstract: Two-year results show that retroiridis-fixated iris-claw aphakic IOL implantation is an effective and safe method with regards to corneal endothelial cell loss, and a new A constant is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 19 publications
5
31
0
3
Order By: Relevance
“…[9] The safety and efficacy of aphakic rehabilitation with retropupillary iris claw fixation has been studied and it has been found to be a safe procedure for rehabilitation of aphakic eyes. [561011] There are very few studies on this procedure in Indian eyes, and hence this study has been conducted. [56]…”
Section: Discussionmentioning
confidence: 99%
“…[9] The safety and efficacy of aphakic rehabilitation with retropupillary iris claw fixation has been studied and it has been found to be a safe procedure for rehabilitation of aphakic eyes. [561011] There are very few studies on this procedure in Indian eyes, and hence this study has been conducted. [56]…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to other published findings which demonstrate that ECL is higher in the first year post aphakic Artisan IOL implantation, with a further drop noted over the subsequent years to a lesser extent-this seems to stabilise 3 years post operatively. 12,19,20 In a multicentre study of Artisan phakic IOL, ECL was found to stabilise 3 years post operatively. 19 It seems that there are two stages for ECL; the intra-operative stage, where most ECL occurs, and 2-3 years post operatively.…”
Section: Eyementioning
confidence: 98%
“…4,15,16 The retropupillary fixated IOL also does not prevent pupil dilation for posterior segment examination and treatment purposes. 14,17 In this case of traumatized PKP, implantation of iris-claw aphakic IOL with retropupillary fixation proved to be a feasible treatment with a good outcome, although the long-term outcome is unknown.…”
Section: Discussionmentioning
confidence: 93%